The mechanism of diagnostics of knowledge - based economy development - Lukianova, N.; Novodon, O. (Przegląd Prawno-Ekonomiczny, 2012)
Streszczenie dostępne wyłącznie w języku angielskim: The mechanism of diagnostics of knowledge based economy progress is developed, stages of diagnostics of knowledge based economy development at the macro-, mezzo- and micro levels are defined with practical concretization of the last one on the basis of information of 5 machine-building enterprises, the necessity for elaboration and approbation of the methodology of the diagnostics of knowledge based economy development at the micro level is substantiated.